Minichine / Nur Naili Hanafi ... [et al.] - Hanafi, Nur Naili; Qian Hui, Chung; Cheng Yuen Yee, Karin; Chui Yee, Loo; Zhi Jie, Teoh (2022)
The environmental effect will occur if every food thrown away at landfill contributes towards pollution through CO2 emission. Food waste is currently one of the largest greenhouse gases (GhG) contributors globally, this results in larger issues such as water pollution, air pollution and climate change. Since the environment is our natural capital which provides raw materials and resources for our life, we should be aware of going green to reduce the amount of food waste that affects the pollution of the environment. It is a future trend as everyone is aware of green intentions to engage in environmental protection.